2011
DOI: 10.1161/strokeaha.110.594705
|View full text |Cite
|
Sign up to set email alerts
|

Immunodepression After Aneurysmal Subarachnoid Hemorrhage

Abstract: Background and Purpose-Immunodepression after stroke is associated with complications like high infection rate, but its role in aneurysmal subarachnoid hemorrhage (aSAH) is unclear. This pilot study aimed to assess the presence of immunodepression and its association with infections after aSAH. Methods-Sixteen aSAH patients were enrolled in a prospective study on immune function in a single institution. Detailed immune monitoring (peripheral blood leukocyte subsets, monocyte human leukocyte antigen-DR expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
96
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(111 citation statements)
references
References 29 publications
8
96
1
1
Order By: Relevance
“…As an anti-inflammatory cytokine, IL-10 has pleiotropic effects: it could not only limit excessive inflammatory response, but also impair T1 helper cells and monocyte functions and induce immunosuppresion (8). The patients with subsequent infections presented a marked loss of lymphocytes and especially CD4+ subsets in our study, and similar results were also revealed in another study (18). A reversed correlation between IL-6 level and CD3 T cells count was also demonstrated in this study.…”
Section: █ Conclusionsupporting
confidence: 89%
“…As an anti-inflammatory cytokine, IL-10 has pleiotropic effects: it could not only limit excessive inflammatory response, but also impair T1 helper cells and monocyte functions and induce immunosuppresion (8). The patients with subsequent infections presented a marked loss of lymphocytes and especially CD4+ subsets in our study, and similar results were also revealed in another study (18). A reversed correlation between IL-6 level and CD3 T cells count was also demonstrated in this study.…”
Section: █ Conclusionsupporting
confidence: 89%
“…It can also be hypothesized that clipped patients are at increased risk to develop immunodepression, which increases the risk of infections after SAH. 9 The higher incidence of seizures in clipped patients was also observed in the International Subarachnoid Aneurysm Trial (ISAT) and most likely results from brain damage secondary to craniotomy. 2 In our study, cardiac arrest occurred in 6.9% of patients and was strongly associated with poor outcome.…”
Section: Vergouwen Et Al Complications After Clipped and Coiled Aneurmentioning
confidence: 93%
“…Patients with SAH with immunodepression might be good candidates to receive prophylactic treatment with antibiotics. 9 Several potential limitations need to be addressed. The reported incidence of in-hospital complications can be limited by ascertainment and interobserver bias.…”
Section: Vergouwen Et Al Complications After Clipped and Coiled Aneurmentioning
confidence: 99%
“…33 The results presented in our study corroborate these findings and suggest that these mechanisms also could be relevant in clinical aSAH. While IFNG has previously been reported in aSAH-induced immune depression, 34 the role of IL-12p70 in aSAH is unclear. The high correlation between IFNG and IL-12p70 in our participant population suggests the presence of a mechanism involving IL-12p70 stimulation of natural killer cells, which in turn express IFNG.…”
mentioning
confidence: 97%